Examining the additivity of peak heights in forensic DNA profiles. Issue 5 (3rd September 2021) - Cheng, Kevin; Bright, Jo-Anne; Kerr, Zane; Taylor, Duncan; Ciecko, Anne; Curran, James; Buckleton, John
ABSTRACT: It is routinely assumed when interpreting forensic DNA profiles that peaks of the same molecular size, whether allelic or stutter in origin, 'stack'. That is, the height of a composite peak is approximately equal to the sum of its parts. There is strong theoretical reason to believe that this assumption should hold across the range of peak heights where fluorescent response is linear with respect to template. However, recent publications have called for empirical proof of, or directly questioned, this assumption. In this study we have examined the heights of allelic, stutter, and composite peaks, and demonstrate that peak heights are reliably predicted as the sum of their individual components. This work supports the long-held belief that peak heights 'stack' in an additive fashion.